Search for low-mass dilepton resonances in Higgs boson decays to four-lepton final states in proton-proton collisions at root s=13 TeV - CMS Collaboration; Damarseçkin, Serdal (SPRINGER, 2022)
A search for low-mass dilepton resonances in Higgs boson decays is conducted in the four-lepton final state. The decay is assumed to proceed via a pair of beyond the standard model particles, or one such particle and a Z boson. The search uses proton–proton collision data collected with the CMS detector at the CERN LHC, corresponding to an integrated luminosity of 137 fb−1, at a center-of-mass energy √s = 13 TeV. No significant deviation from the standard model expectation is observed. Upper limits at 95% confidence level are set on model-independent Higgs boson decay branching fractions. Additionally, limits on dark photon and axion-like particle production, based on two specific models, are reported.